A spectral critique of Hong Kong films: a reading of the urban spectre: Dr. Esther MK Cheungs essays in Hong Kong film studies - Ng, Kok-Hwa (Tanjong Malim, 2021)
A spectral critique of Hong Kong films: a reading of the urban spectre: Dr. Esther MK Cheungs essays in Hong Kong film studies by Ng, Kok-Hwa